1969
DOI: 10.12669/pjms.301.4129
|View full text |Cite
|
Sign up to set email alerts
|

Hematological profile and risk factors associated with pulmonary tuberculosis patients in Quetta, Pakistan.

Abstract: Objectives: Tuberculosis (TB) is a chronic debilitating infectious disease affecting more than one third of the global population. This study was designed to investigate different peripheral blood parameters and risk factors in TB patients. Methods: A total of 600 (Male, 238 and Female, 362) aging 20-80 Years patients with clinical signs of prolonged cough, chest pain and fever, were evaluated for peripheral blood parameters using hematology analyzer. All the informations related to the disease were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
37
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 0 publications
10
37
1
1
Order By: Relevance
“…Females were 63.5% in smear positive cases in this study. The present study was in line with other previous studies, in which females were more affected by tuberculosis than males (22)(23)(24)(25)(26)(27). Zaman et al and Akhtar et al also noted that tuberculosis was more prevalent in females than in males (21,28).…”
Section: Discussionsupporting
confidence: 93%
“…Females were 63.5% in smear positive cases in this study. The present study was in line with other previous studies, in which females were more affected by tuberculosis than males (22)(23)(24)(25)(26)(27). Zaman et al and Akhtar et al also noted that tuberculosis was more prevalent in females than in males (21,28).…”
Section: Discussionsupporting
confidence: 93%
“…Disease in this study was found in all age groups equally but was highest in productive and mature age group of 21-40 years which is (46.76%). Finding of this study was in line with previous study by (20)(21)(22) who reported that tuberculosis is a disease of adult productive 20-50 years age group.…”
Section: Discussionsupporting
confidence: 93%
“…Both CRP and ESR are established prognostic indicators in patients with pulmonary TB; CRP is an acute phase indicator of inflammation that reflects the disease severity [34], while ESR is regarded as an indicator of disease activity, and is also reflective of disease severity [35]. In agreement with the literature, CRP levels and the ESR were elevated in patients with sputum positivity in this study.…”
Section: Cellular Physiology and Biochemistrysupporting
confidence: 89%